Othello / edited by E.A.J. Honigmann. - Honigmann, E. A. J.; Shakespeare, William, 1564-1616 (Arden Shakespeare. Third series., 2016)
This second edition of 'Othello' has a new, illustrated introduction by leading American scholar Ayanna Thompson, which addresses such key issues as race, religion and gender, as well as looking at ways in which the play has been adapted in more recent times.